Reaksi Pemasaman Senyawa Pirit pada Tanah Rawa Pasang Surut - Priatmadi, Bambang Joko; Haris, Abdul (UNIVERSITY OF LAMPUNG, 2009)
Most of swamp soils in tidal land are Acid Sulfate Soils. Acid sulfate soils are the common name given to soils containing iron sulfides (pyrite). The soils are characterized by very low pH and high amount of soluble S and Fe, resulted from oxidation of pyrite when soils are drained. This study was aimed to determine acidity pattern, iron and sulfate solubility as the impact of the length time of oxidized, the effect of inhibitors application to acidity rate of sulfidic materials and top soils. The materials are: (1) soils at pyritic layer (sulfidic materials) and (2) soils at 0 – 20 cm from soil surface. Soils is sampled at Barambai reclaimed area, Barito Kuala Regency, South Kalimantan Province. In the laboratory soils treated with some ameliorants, that are silica, phosphate and lime applied with dosage 2 t ha-1 with 3 replications times. The soils incubated for 2 weeks under submerged condition. After soil incubation, soil exposed to the air for 1 week, 2 weeks, 4 weeks, and 6 weeks. Parameters of soil analysis include pH, sulfate and iron soluble. Results of this study showed that (1) soil acidity rate of sulfidic materials more faster than upper soils when soils and sulfidic materials oxidized intensively, (2) at submerged soil condition or high soil water content, the application of ameliorants effective increasing the soil pH of the upper soils, (3) at further oxidized soil condition or lower soil water content, the application of ameliorants inhibited acidity rate of soils and sulfidic materials, and (4) at further oxidized soil condition or lower soil water content, the application of ameliorants increased iron solubility of soils and sulfidic materials.